Support needs of carers making proxy healthcare decisions for people with dementia: a systematic review based on the Noblit and Hare meta-ethnographic synthesis of qualitative studies. Issue 12 (20th December 2021) - Hodges, Victoria; Hynes, Catherine; Lassa, Samuel; Mitchell, Caroline
Abstract : Background: There are 50 million dementia sufferers worldwide. Decisions about healthcare often need to be made when the person with dementia lacks capacity to do so. Understanding the support needs of carers acting as proxy healthcare decision-makers will be vital in improving the decision-making process for people with dementia and addressing the holistic needs of carers. Objective: The objective of this study was to review the existing literature on the support needs of carers acting as proxy healthcare decision-makers for people with dementia. Design: A qualitative systematic review protocol was published on PROSPERO. The Critical Appraisal Skills Programme checklist was used to appraise study quality. A meta-ethnographic synthesis was performed to develop third-order constructs. Data sources: A search was conducted using three online databases (MEDLINE, CINAHL and PsycINFO). Eligibility criteria: Fifteen studies met the inclusion criteria: primary qualitative research involving carers of people with dementia who had been involved in making proxy healthcare decisions. Data extraction and synthesis: Two independent researchers conducted validity assessments for each paper selected for inclusion, and discrepancies were resolved by discussions with a third reviewer. Nvivo software was used and conceptual findings from study papers lead to interpretations of findings by the team. Results: From the 15 papers included in the study, three main domains arose from the meta-ethnography; informational, practical and emotional. Informational support needs included information about dementia itself and the anticipated disease trajectory. Practical needs included continuity of care, person-centred care and the use of legal frameworks. Emotional support included recognising the guilt that healthcare decisions can provoke and the importance of providing guidance in an empathic manner. Conclusions: This meta-ethnography highlights opportunities for healthcare professionals and policymakers to improve experiences of carers making proxy healthcare decisions for people with dementia. PROSPERO registration number: CRD42020124485.